Biomass Turnover Rates in Metabolically Active and Inactive Marine Calanoid Copepods - Mayor, Daniel J.; Cook, Kathryn B.; Thornton, Barry; Atherden, Florence; Tarling, Geraint A.; Anderson, Thomas R. (Frontiers in Marine Science, 2022)
Lipid-storing copepods are fundamental to the functioning of marine ecosystems, transferring energy from primary producers to higher trophic levels and sequestering atmospheric carbon (C) in the deep ocean. Quantifying trophic transfer and biogeochemical cycling by copepods requires improved understanding of copepod metabolic rates in both surface waters and during lipid-fueled metabolism over winter. Here we present new biomass turnover rates of C and nitrogen (N) in Calanoides acutus, Calanoides natalis, Calanus glacialis and Calanus hyperboreus alongside published data for Calanus finmarchicus and Calanus pacificus. Turnover rates in metabolically active animals, normalised to 10°C, ranged between 0.007 – 0.105 d-1 and 0.004 – 0.065 d-1 for C and N, respectively. Turnover rates of C were typically faster than those for N, supporting the understanding that non-protein C, e.g. lipid, is catabolised faster than protein. Re-analysis of published data indicates that inactive, overwintering C. finmarchicus turn over wax ester lipids at a rate of 0.0016 d-1. These and other basal rate data will facilitate the mechanistic representation of copepod physiology in global biogeochemical models, thereby reducing uncertainties in our predictions of future ocean ecosystem functioning and C sequestration.